Liberalising discrimination law: Why the Equality Act is unfit for purpose - Daniel Freeman; Alex Morton (Institute of Economic Affairs (IEA), 2025)
Over the past six decades our political, philosophical and legal approaches to discrimination have evolved, moving from a laissez-faire attitude to complex legislation that addresses both 'direct' and 'indirect' discrimination. Some argue now for the complete abolition of anti-discrimination legislation, reverting to free market principles. On the other hand, others argue that we need to go further in attacking indirect discrimination through the law. This paper makes the case that while liberals can accept outlawing direct discrimination under the concept of equality before the law, or a laissez faire approach, going further than these approaches will invariably lead to bad outcomes. Progressive structural and anti-racist approaches that treat individuals differently due to their race in order to equalise group outcomes amplify divisions and promote illiberal agendas. Such approaches fail minority individuals who are genuinely disadvantaged and overturn the principle of equal treatment for all individuals before the law. The Equality Act should return to the roots of earlier legislation, by outlawing direct discrimination focused on individuals rather than remove or reduce gaps between groups. The rest of the Act should be removed from the statute books. This would be a genuinely liberal but strong anti-discrimination agenda.
Keywords: 330